2012
DOI: 10.5194/acpd-12-32631-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intercomparison of shortwave radiative transfer schemes in global aerosol modeling: results from the AeroCom Radiative Transfer Experiment

Abstract: In this study we examine the performance of 31 global model radiative transfer schemes in cloud-free conditions with prescribed gaseous absorbers and no aerosols (Rayleigh atmosphere), with prescribed scattering-only aerosols, and with more absorbing aerosols. Results are compared to benchmark results from high-resolution, multi-angular line-by-line radiation models. For purely scattering aerosols, model bias relative to the line-by-line models in the top-of-the atmosphere aerosol radiative forcing ranges from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 103 publications
(61 reference statements)
1
25
0
Order By: Relevance
“…Mie optical parameters for aerosols are computed using wavelength-dependent refractive indices from the OPAC database and the aerosol size distributions from the ULAQ model. The ULAQ model's photolysis rates, surface and top-of-atmosphere radiative fluxes have been validated in the framework of SPARC-CCMVal and AeroCom inter-comparison campaigns [75,76].…”
Section: Ulaq Radiative Transfer Modelmentioning
confidence: 99%
“…Mie optical parameters for aerosols are computed using wavelength-dependent refractive indices from the OPAC database and the aerosol size distributions from the ULAQ model. The ULAQ model's photolysis rates, surface and top-of-atmosphere radiative fluxes have been validated in the framework of SPARC-CCMVal and AeroCom inter-comparison campaigns [75,76].…”
Section: Ulaq Radiative Transfer Modelmentioning
confidence: 99%
“…However, the code used has recently been included in an intercomparison study by Randles et al (2012), and this demonstrated that the uncertainty compared to state-of-the-art radiative transfer models is likely around 1-2 % for the TOA radiative flux. This is considerably smaller than most of the other sources considered here.…”
Section: Aerosol Radiative Effect Calculationsmentioning
confidence: 99%
“…The setup is designed to be as simple as possible to illustrate the effect of SSA and size distribution on radiative fluxes and atmospheric heating rates; further studies will employ more detailed radiative transfer models. We use the Edwards and Slingo radiative transfer model (Edwards and Slingo, 1996;Randles et al, 2012) with a plane-parallel atmosphere and model irradiance from 0.2 to 10 µm with 220 spectral bands. A standard tropical atmosphere was used for vertical profiles of atmospheric gases (Anderson et al, 1986).…”
Section: Radiative Transfer Calculationsmentioning
confidence: 99%